Tailoring the Diagnostic Pathway for Medical and Surgical Treatment of Uterine Fibroids: A Narrative Review - Gabriele Centini; Alberto Cannoni; Alessandro Ginetti; Irene Colombi; Matteo Giorgi; Giorgia Schettini; Francesco Giuseppe Martire; Lucia Lazzeri; Errico Zupi (Diagnostics)
Uterine leiomyomas are the most common benign uterine tumors in women and are often asymptomatic, with clinical manifestation occurring in 20–25% of cases. The diagnostic pathway begins with clinical suspicion and includes an ultrasound examination, diagnostic hysteroscopy, and, when deemed necessary, magnetic resonance imaging. The decision-making process should consider the impairment of quality of life due to symptoms, reproductive desire, suspicion of malignancy, and, of course, the woman’s preferences. Despite the absence of a definitive cure, the management of fibroid-related symptoms can benefit from various medical therapies, ranging from symptomatic treatments to the latest hormonal drugs aimed at reducing the clinical impact of fibroids on women’s well-being. When medical therapy is not a definitive solution for a patient, it can be used as a bridge to prepare the patient for surgery. Surgical approaches continue to play a crucial role in the treatment of fibroids, as the gynecologist has the opportunity to choose from various surgical options and tailor the intervention to the patient’s needs. This review aims to summarize the clinical pathway necessary for the diagnostic assessment of a patient with uterine fibromatosis, presenting all available treatment options to address the needs of different types of women.